SOSIALISASI DAMPAK STUNTING PADA BALITA DI DESA PASIE JAMBU KECEMATAN KAWAI IXV KABUPATEN ACEH BARAT - Susy Sriwahyuni; Khairunnas Khairunnas (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2020)
Malnutrition is the worst form of the process of chronic malnutrition. Healthy toddlers or malnourished children can simply be known by comparing the weight according to age with the reference (standard) that has been set. If the weight according to age matches the standard, the child is called good nutrition. If it is slightly below standard, it is called malnutrition If it is far below the standard, it is called malnutrition. According to the Aceh Ministry of Health, in 2017 there were around 27.5% (5 million undernourished children), 3.5 million children (19.2%) underweight and 1.5 million malnourished children (8.3% ). WHO in 2008 grouped regions based on the prevalence of malnutrition into four groups, namely low (<10%), moderate (10-19%), high (20-29%) and very high (> 30%). Servitude of  this using descriptive methods that describe the results of devotion made and socializing the danger of malnutrition to toddlers to the community in Pasie Jambu village. The implementation of the socialization program was attended by the community and community leaders. The number of people who participated in the socialization program were 30 people.